High intrinsic catalytic activity of two-dimensional boron monolayers for the hydrogen evolution reaction. Issue 2 (14th December 2016) - Shi, Li; Ling, Chongyi; Ouyang, Yixin; Wang, Jinlan
Abstract : 2D boron monolayers as a new class of candidates are active catalysts for HER, as well as metallic conductivity and plenty of active sites in the basal plane. Abstract : Two-dimensional (2D) boron monolayers have been successfully synthesized on a silver substrate very recently. Their potential application is thus of great significance. In this work, we explore the possibility of boron monolayers (BMs) as electrocatalysts for the hydrogen evolution reaction (HER) by first-principles methods. Our calculations show that BMs are active catalysts for HER with nearly zero free energy of hydrogen adsorption, metallic conductivity and plenty of active sites in the basal plane. The effect of the substrate on HER activity is further assessed. It is found that the substrate has a positive effect on the HER performance caused by the competitive effect of mismatch strain and charge transfer. The in-depth understanding of the structure dependent HER activity is also provided.